Thomas Chatterton, the Marvelous Boy : With "The Exhibition," a Personal Satire - Ellinger, Esther Parker (Philadelphia : University of Pennsylvania Press, 1930)
A psychological analysis of Chatterton's contradictory mental characteristics, with the first complete publication of his violent verses against the citizens of Bristol.
Frontmatter -- Contents -- I -- II -- Notes -- The Exhibition
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Jan 2018).
JSTOR
Keywords: Chatterton, Thomas, -- 1752-1770.; Chatterton, Thomas, -- 1752-1770; Literary forgeries and mystifications -- History -- 18th century; Poets, English -- 18th century -- Biography; Faux et supercheries littéraires -- Histoire -- 18e siècle.; Poètes anglais -- 18e siècle -- Biographies; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literary forgeries and mystifications; Poets, English; 1700-1799; Cultural Studies; Literature; Biographies; History